A comprehensive analysis of Ardisia crenata Sims from endophytes and rhizosphere soil microorganisms - Liu, Chang; Luo, Jiangli; Yang, Demei; Liu, Xiongwei; Zhou, Sixuan; Zhou, Ying (Frontiers in Microbiology, 2025)
IntroductionEndophytic and rhizosphere microorganisms play crucial roles in influencing the quality and secondary metabolite accumulation of traditional Chinese medicinal.MethodsEndophytic and rhizosphere microorganisms play crucial roles in influencing the quality and secondary metabolite accumulation of traditional Chinese medicinal.Results and discussionA total of 8,514,557 highquality reads were generated from 140 plant and soil sample in A. crenata Sims based on high-throughput sequencing. The fungal species composition within the endophytic and rhizosphere soil samples of A. crenata Sims is rich and varied, exhibiting notable disparities across different geographical regions of the plant. The alpha diversity and beta diversity indicated significant differences in microbial diversity and community structure between soil and plants. As for endophytic fungi, the dominant phyla in both plants and soil were Ascomycota and Basidiomycota, with different dominant genera between the two compartments. LEfSe analysis at the genus level identified 80 and 124 fungal indicator taxa associated with plants and soil, respectively, including Aspergillus, Acremonium, Fusarium, among others. Co-occurrence network analysis demonstrated intimate interactions among soil fungal microorganisms. Examination of soil physicochemical factors and the primary active constituent (bergenin) across different regions of A. crenata Sims indicated that the highest bergenin concentration is found in the Guangxi region, whereas the Guizhou region boasts relatively abundant soil nutrient components. Correlation analysis revealed that Aspergillus, Fusarium, Penicillium, Tausonia, and Trichoderma are correlated with soil physicochemistry or active compounds. These findings hint at a potential role for endophytic and rhizosphere microorganisms in the accumulation of active compounds within medicinal plants, thereby furnishing a scientific rationale for guiding the cultivation practices of A. crenata Sims.